Market and inequality revisited - Alejandro F. Mercado; Tirza J. Aguilar (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2006)
The great controversy regarding the results of the application of market-oriented policies on the population's conditions of life, especially about the inequality in the distribution of income, has constituted the concern that has given origin to this paper. With the objective to test the hypothesis that a free market structure promotes a better income distribution, we have carried out several quantifications of inequality indices in the different structures of the labor market in Bolivia; also, a microsimulation model has been applied, to see whether change toward a market-oriented structure can improve the distribution of income and, lastly, we have carried out an exercise to link income inequality with social mobility. The reached results, although they are not the sufficiently strong to validate the hypothesis, are sufficiently clear to show us that the free market policies do not act in a negative way on the income distribution. – – La gran controversia respecto a los resultados de la aplicación de políticas orientadas al mercado sobre las condiciones de vida de la población, en especial sobre la desigualdad en la distribución del ingreso, ha constituido la preocupación que ha dado origen a este trabajo. Con el objetivo de testear la hipótesis de que una estructura de libre mercado promueve una mejor distribución del ingreso, hemos realizado varias cuantificaciones de índices de desigualdad en las distintas estructuras del mercado laboral en Bolivia; asimismo, se ha aplicado un modelo de microsimulación, para ver en qué medida un cambio hacia políticas orientadas al mercado pueden mejorar la distribución del ingreso y, por último, se ha realizado un ejercicio para vincular la desigualdad del ingreso con la movilidad social. Los resultados alcanzados si bien no son lo suficientemente fuertes para validar la hipótesis, son lo suficientemente claros para mostrarnos que las políticas de libre mercado no actúan de manera negativa sobre la distribución del ingreso.
Keywords: 330; Marktmechanismus; Einkommensverteilung